2012
DOI: 10.1590/s1516-44462012000100011
|View full text |Cite
|
Sign up to set email alerts
|

Peritraumatic tonic immobility is associated with posttraumatic stress symptoms in undergraduate Brazilian students

Abstract: This automatic reaction under extreme life threatening stress, although adaptive for defense, may have pathological consequences as implied by its association with PTSD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Based on TI Scale (TIS-C: Forsyth et al, 2000), we used a four-item measure of motor aspects of TI which has been validated (Lima et al, 2010) and employed in previous studies (Rocha-Rego et al, 2009; Volchan et al, 2011; Portugal et al, 2012): (i) froze or paralyzed; (ii) unable to move; (iii) unable to call out or scream, and (iv) unable to escape. Total scores range from zero to 24.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on TI Scale (TIS-C: Forsyth et al, 2000), we used a four-item measure of motor aspects of TI which has been validated (Lima et al, 2010) and employed in previous studies (Rocha-Rego et al, 2009; Volchan et al, 2011; Portugal et al, 2012): (i) froze or paralyzed; (ii) unable to move; (iii) unable to call out or scream, and (iv) unable to escape. Total scores range from zero to 24.…”
Section: Methodsmentioning
confidence: 99%
“…For retrospective reports, in a large epidemiological sample, greater TI scores were found to be associated with PTSD (Kalaf et al, 2015). Other studies observed that retrospective reports of peritraumatic TI are correlated with the severity of PTSD symptoms (Fiszman et al, 2008; Rocha-Rego et al, 2009; Lima et al, 2010; Portugal et al, 2012; Maia et al, 2015; Kleine et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Along with other peritraumatic stress reactions, TI has been reported as a risk factor for Posttraumatic Stress Disorder – PTSD [10], [14], [15]. Fiszman et al [11] showed that among victims of violence TI predicted the severity of posttraumatic stress symptoms, as well as a poor response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The tonic immobility response has been documented in animals for more than three centuries ( Maser and Gallup, 1977 ). In humans, studies have demonstrated that tonic immobility also occurs, especially during a life-threatening event ( Suarez and Gallup, 1979 ; Galliano and Noble, 1993 ; Heidt et al, 2005 ; Fusé et al, 2007 ; Bados et al, 2008 ; Bovin et al, 2008 ; Abrams et al, 2009 ; Humphreys et al, 2010 ; Portugal et al, 2012 ). Recently, studies found that tonic immobility was a predictor of the severity of posttraumatic stress disorder (PTSD) symptoms and of poor response to pharmacological treatment in PTSD patients who had been exposed to urban violence ( Fiszman et al, 2008 , Rocha-Rego et al, 2009 ; Lima et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies found that tonic immobility was a predictor of the severity of posttraumatic stress disorder (PTSD) symptoms and of poor response to pharmacological treatment in PTSD patients who had been exposed to urban violence ( Fiszman et al, 2008 , Rocha-Rego et al, 2009 ; Lima et al, 2010 ). Moreover, tonic immobility was significantly associated with PTSD symptoms in a non-clinical sample ( Portugal et al, 2012 ). Taken together, these studies suggest that the occurrence of this defensive reaction is not uncommon in humans and its occurrence might reflect how intense the traumatic event is perceived by the individual.…”
Section: Introductionmentioning
confidence: 99%